2018
DOI: 10.1186/s40494-018-0217-y
|View full text |Cite
|
Sign up to set email alerts
|

Materials and techniques of Islamic manuscripts

Abstract: Over 50 works on paper from Egypt, Iraq, Iran and Central Asia dated from the 13th to 19th centuries were examined and analyzed at the Straus Center for Conservation and Technical Studies. Forty-six of these were detached folios, some of which had been removed from the same dispersed manuscript. Paintings and illuminations from five intact manuscripts were also examined and analyzed, although not all of the individual works were included. The study was undertaken to better understand the materials and techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 22 publications
2
31
0
3
Order By: Relevance
“…These findings are in agreement with the characterization of basic copper chlorides in the 15th century Catalonia and the Crown of Aragon paintings (oil and tempera paintings), systematically studied by Salvadó et al [10,11]. They are also in agreement with what observed by Eremin et al in a recent study on Islamic manuscripts [12], in which certain shades of green only present atacamite.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are in agreement with the characterization of basic copper chlorides in the 15th century Catalonia and the Crown of Aragon paintings (oil and tempera paintings), systematically studied by Salvadó et al [10,11]. They are also in agreement with what observed by Eremin et al in a recent study on Islamic manuscripts [12], in which certain shades of green only present atacamite.…”
Section: Discussionsupporting
confidence: 92%
“…We tested this variation because we know that many craft recipes have not been documented in written sources, but were part of an anonymous craft "savoir faire" that has been lost. It was very exciting to find that this kind of formulation was detected in works of art ranging from panel painting to medieval illuminations, and from Europe to Persia [10][11][12][13]. We consider that one of our main contributions lies in the integration of our knowledge on craft recipes that describe the manufacture and preparation of paint materials with the state-of-the-art research on the mechanisms of atmospheric corrosion of metals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional case studies include two articles published by separate research groups, one in France (Denoël et al [13]) and one in Austria (Frühmann et al [14]), discussing eighth-and ninth-century manuscripts from Carolingian scriptoria; the Emerson-White Book of Hours, whose late fifteenth-century Flemish illuminations were investigated by Mayer et al [15]; and a study of the materials used in other parts of manuscripts, such as the decoration of the sunk-panel binding of a Venetian 'Commissione Dogale' , reported by Rampazzo and Di Foggia [16]. A survey of the materials used in over 50 Islamic manuscripts, carried out by Knipe et al [17], significantly expands the geographic origin of the original material investigated and emphasises the importance of moving beyond the well-known Western European tradition of manuscript Finally, the complex mathematical methods used by Calatroni et al [18] for the digital 'restoration' and interpretation of manuscripts-and their provision of additional multi-media content linked to the published article-serve to bring cross-disciplinary research on medieval manuscripts fully into the digital era.…”
mentioning
confidence: 99%
“…There are few studies on paper reported which is an important medium over the centuries [19]. We have recently published a very substantive study of Islamic manuscripts [20]. South America is also on this list, with several primarily archaeometric studies [21].…”
mentioning
confidence: 99%